Zinc supplementation influences genomic stability biomarkers, antioxidant activity, and zinc transporter genes in an elderly Australian population with low zinc status. Issue 6 (13th May 2015) - Sharif, Razinah; Thomas, Philip; Zalewski, Peter; Fenech, Michael
<x xml:space="preserve">Abstract</x> Scope An increased intake of Zinc (Zn) may reduce the risk of degenerative diseases but may prove to be toxic if taken in excess. This study aimed to investigate whether zinc carnosine supplement can improve Zn status, genome stability events, and Zn transporter gene expression in an elderly (65–85 years) South Australian cohort with low plasma Zn levels. Methods and results A 12‐week placebo‐controlled intervention trial was performed with 84 volunteers completing the study, (placebo, n = 42) and (Zn group, n = 42). Plasma Zn was significantly increased (p < 0.05) by 5.69% in the Zn supplemented group after 12 weeks. A significant (p < 0.05) decrease in the micronucleus frequency (−24.18%) was observed for the Zn supplemented cohort relative to baseline compared to the placebo group. Reductions of −7.09% for tail moment and −8.76% for tail intensity were observed for the Zn group (relative to baseline) (p < 0.05). Telomere base damage was found to be also significantly decreased in the Zn group (p < 0.05). Both MT1A and ZIP1 expression showed a significant increase in the Zn supplemented group (p < 0.05). Conclusion Zn supplementation may have a beneficial effect in an elderly population with low Zn levels by improving Zn status, antioxidant profile, and lowering DNA damage.